An unusual radiological presentation of pulmonary Langerhans’ cell histiocytosis - Burr, Lucy (BMJ Case Rep, 2012)
Langerhans’ cell histiocytosis is a proliferative disease of the dendritic cell lineage. It usually has a characteristic radiological presentation of apical nodules and small cysts occurring predominantly in young adult smokers. Here we report a case of multisystem Langerhans cell histiocytosis in a 75-year-old woman with unusual chest radiology.